Consumer Acceptance of Local Protein-Based Ready-to-Eat Products Processed with Retort Technology to Support Food Security - Wandi Kurniadi; Evi Sofiati (Journal of Food Security and Agroindustry, 2026)
Ready-to-eat (RTE) food based on local protein can broaden practical food choices and support food security through local resources. This study examined consumer acceptance of a retort-processed RTE prototype made from snakehead fish (Channa striata) and tempeh. The study used an experimental approach with three formulations based on the ratio of snakehead fish to tempeh, namely F1 (80:20), F2 (60:40), and F3 (40:60). Seventy-five semi-trained panelists evaluated color, aroma, texture, taste, and overall acceptance using a five-point hedonic scale. Hedonic data were analyzed using the Friedman test, while Kendall's W was used to describe the effect size. The F2 formulation achieved the highest mean scores for all attributes, including color (3.82), aroma (3.65), texture (3.71), taste (3.94), and overall acceptance (3.78). The Friedman test indicated differences among formulations in aroma, texture, taste, and overall acceptance, while color showed no difference. These findings suggest that a 60:40 ratio of snakehead fish and tempeh provides the most acceptable sensory profile. The practical contribution of this study is the identification of a local protein-based RTE formulation that can be further developed for food diversification. However, F0 value, come-up time, cooling time, packaging size, microbiological safety, shelf life, and production cost still require further assessment before commercial application.